SYNCRETIZATION OF CHINESE RELIGION IN SINGKAWANG WEST KALIMANTAN - Samsul Hidayat (Graduate Program of Pontianak Institute of Islamic Studies, 2012)
This paper attempts to shed light on the context of religiosity which is very pluralistic and dynamic in Indonesia. It is based on the field research conducted in Singkawang focusing on the Chinese religion. Some important conclusions could be drawn here such as the syncretization of the Chinese religion concerning the understanding of the existence of God and the gods which often has overlapping hierarchy including syncretic perspectives on understanding cosmology, mythology, symbols associated with mystical tales and supernatural beings. In the process, many Chinese Indonesians in Singkawang who are demographically Buddhists, Christians, or Muslims, still perform a pattern of worship of Confucianism or Taoism in their daily lives. The procedure of worship has also been modified so that its format differs from that found outside Indonesia. Meanwhile, during the celebration of the Chinese lunar new year and Cap Go Meh (the fifteenth night), Chinese Indonesians in Singkawang perform a ritual to get rid of bad luck. It is a unique, syncretic ‘collaboration’ between Chinese traditions and local culture. Keywords: Syncretization, Religion, Chinese, Singkawang.